Análise do gerenciamento de resíduos: estudo em empresas do arranjo produtivo local metal centro - Jacques, Elizeu de Albuquerque (2015)
In the scenery where metal-mechanic organizations work, the constant use of material that generate waste is observed and this represents a continuous challenge to the companies, through the compatibility to the operational activity exercise with the preservation of the natural resources. Considering such perspective, the management of wastes is a systemic strategy in the context of operational activities maintenance. This study aims at analyzing the procedures of management waste in companies that belongs to the Local Productive Arrangement Metal Centro, whose work field is in the central region of Rio Grande do Sul. The methodological strategy adopted is characterized, the method, as an applied case study of exploratory mode and analysis of data in a qualitative approach. In order that the study could be accomplished, procedures and techniques of data collection were used. For doing so, documental research and interviews were used and they enabled the achievement of necessary information to the leading of the proposal investigation. Thus, the waste generated in the productive process of the companies, were identified and classified to enable the proposition of actions and strategies with the purpose to minimize the waste generation and the improvement of sustainable alternatives. In the procedures of study focused on the context of activities developed by the companies of metal mechanic section, it was identified the possibility of implementation of improvement strategies in the use of materials in the productive process. Such strategies can be individually developed through the procedures, techniques and utilization of equipment that provide the reduction of the waste generation. Besides, such strategies can also be collectively developed by the companies and, as consequence, become opportunities of development of joint actions. For example, the joint actions could be the implementation of a unit of managing waste, the development of an integrated database of waste as well as the elaboration of projects to use the available resources by FUNDOAPL to sustainable actions to be implanted by companies. These actions, thought to minimize the generation of waste in the productive process, can provide sustainable strategies and as well as enable a financial return throughout the activities developed by the companies that are member of Local Productive Arrangement Metal Centro.